“We Were Among the First Non-traditional Families”: Thematic Perceptions of Lesbian Parenting After 25 Years - Gartrell, Nanette; Rothblum, Esther D.; Koh, Audrey S.; van Beusekom, Gabriël; Bos, Henny (Frontiers in Psychology, 2019)
In the sixth wave of the U.S. National Longitudinal Lesbian Family Study, when their offspring were 25 years old, the parents were asked to reflect on their most challenging and best experiences raising children in nontraditional families. The responses of 131 parents were interpreted through thematic analysis. The most challenging parenting experiences fell into five major categories: 1) distress about their children’s experiences of exclusion, heterosexism, or homophobic stigmatization; 2) family of origin nonacceptance of their lesbian-parent family; 3) the never-ending process of “educating the world about queer parents”; 4) homophobia or hostility toward their nontraditional family; and 5) lack of legal protections for sexual minority parent families. Their best parenting experiences included: 1) being role models, leading to a greater acceptance of LGBTQ people; 2) treasuring the LGBTQ parent and family community; 3) teaching their children to appreciate diversity of all types; and 4) witnessing their child’s pride in their nontraditional family. Some of these challenges were anticipated by the parents more than a quarter century ago at the time that they were inseminating or pregnant with the index offspring.